Partners in the global society of the future - Richard F. Behrendt (Intereconomics, 1967)
INTERECONOMICS has repeatedly published the opinion that the main objective of development aid has to be the raising of the standard of living in the developing countries without influencing the socio-economic structure of the recipient countries. This view is opposed by the well-known development expert Professor Behrendt of the Free University of Berlin. We here want to open a discussion upon this opinion.
Keywords: 330; Socio-Political Shift In Developing Countries